A Prospective Cohort Study Showing No Association Between Serum Sclerostin Level and Mortality in Maintenance Hemodialysis Patients - Madoka Sato; Norio Hanafusa; Hiroshi Kawaguchi; Ken Tsuchiya; Kosaku Nitta (Karger Publishers, 2018)
Background/Aims: Potential relationships between serum sclerostin levels and the levels of bone metabolic markers in maintenance hemodialysis (MHD) patients have yet to be evaluated. This study sought to determine whether serum sclerostin levels are associated with mortality in MHD patients. Methods: We measured serum sclerostin levels in a Japanese MHD cohort, classified the patients into tertiles according to these levels, and followed their course for a 42-month period. Results: The cohort consisted of 389 MHD patients and there were 75 deaths. Kaplan-Meier analyses showed that the tertile of serum sclerostin was not associated with mortality risk. Cox analyses showed that there were no significant associations between serum sclerostin level and mortality. Conclusion: Serum sclerostin level was not an independent predictor of mortality in MHD patients after adjustment for several confounders. However, whether clinical interventions to modulate serum sclerostin levels in MHD patients would improve their survival remains to be determined.